Evaluation of a Novel Powered Air-purifying respirator (PAPR) vs. a N95 Respirator Mask for the Protection Against Influenza in a Human Exposure Model. (4th October 2017) - Bischoff, Werner; Turner, Jolyn; Russell, Gregory Bryan; Blevins, Maria; Stehle, John
Abstract: Background: Little is known about the effectiveness of PAPRs against airborne viral pathogens. We compared a novel PAPR (Celios Respirator) to a commercially available N95 respirator (Kimberly Clark, N95 duckbill respirator) using a human exposure model. Methods: Healthy participants were randomized to a PAPR or a N95 exposure group. After consent and qualitative fit-testing (3M, FT-10) nasal swabs (NS) were obtained from each participant to establish absence of Influenza virus before exposure. Participants were asked to dress-up in disposable attire and don the respective devices and airtight goggles. After placement in a test chamber and an evacuation run of 5 minutes of a HEPA air filtration unit, subjects were exposed to Live Attenuated Influenza Vaccine (LAIV 2015/16; 2 × 10 6.5–7.5 fluorescent focus-forming units) aerosolized (Airial MQ5800) for 20 minutes. During the exposure, participants did a standardized set of movements and reading exercises to mimic normal daily usage. NS samples were collected following an evacuation run of the test chamber. Pre- and post-exposure RT-PCR readings of the samples were compared (exact 95% confidence intervals [CIs]). Results: A total of 58 healthy participants were exposed to LAIV (mean age: 31 [age range: 21–49]; male: 33%). Influenza virus was detected in three subjects after exposure wearing N95 respirators (10%; n = 29; 95% CI: 2%, 27%). No virus was found in subjects wearing the PAPR ( n = 29; 95% CI: 0, 12%). The difference in rates is not significant (10% difference, P = 0.24, 95% CI: -17%, 37%). The three subjects with virus detection included two Caucasian males (ages 31 and 40) and one African American female (age: 23). No adverse events were noted during the trial. Conclusion: The novel PAPR provided full protection against aerosolized LAIV. However, 10% of test subjects carried detectable levels of Influenza virus in the upper respiratory tract when using an N95 respirator. The breaches in protection occurred despite passing thorough fit-testing and wearing airtight eye protection to eliminate trans-ocular transmission. The findings provide additional insight when determining criteria for the selection of effective respiratory protection against current and emerging viral pathogen threats. Disclosures: W. Bischoff, Celios: Research Contractor, Research grant and Speaker honorarium.